Social development policies and programs in the Philippines focus on the delivery of health services - Pilar, Nestor N. (Philippine Journal of Public Administration, 1978)
As embodied in the Four-Year National Development Plan and in the sectoral plans, social development is a major thrust of the government. To meet the socioeconomic objective of uplifting the quality of life of the people, the government undertook new health programs such as family planning, nutrition and medicare, sought to provide skills and better education, housing, labor services,harnessed private sector participation in publicly-initiated programs and created coordinating mechanisms to monitor all these programs. Private sector participation particularly in the field of population and nutrition has been institutionalized through the formation of "centers" which serve as a link between national and local agencies. Rural health services were strengthened through the addition of new rural health units, the fielding of mobile teams, and the deployment of health personnel through the restructured health care delivery system and the rural health practice program. Problems of inadequate funds, personnel and logistical support continually beset the rural health units. Case studies on health services in the provinces of Batangas and Bataan indicated problems of outreach due to lack of health manpower and perceptible overloading of health personnel in the field and the uneven distribution of rural health units.